Treatments of faecal incontinence: recommendations from the French National Society of Coloproctology. (March 2014) - Vitton, V.; Soudan, D.; Siproudhis, L.; Abramowitz, L.; Bouvier, M.; Faucheron, J.‐L.; Leroi, A.‐M.; Meurette, G.; Pigot, F.; Damon, H.
Abstract Faecal incontinence is common and significantly affects quality of life. Its treatment involves dietary manipulation, medical treatments, perineal rehabilitation or surgery. In this paper, the French National Society of Coloproctology offers recommendations based on the data in the current literature, including those on recently developed treatments. There is a lack of high quality data and most of the recommendations are therefore based either on grade of recommendation B or expert recommendation (Level 4). However, the literature supports the construction of an algorithm based on the available scientific evidence and expert recommendation which may be useful in clinical practice. The French National Society of Coloproctology proposes a decision‐making algorithm that includes recent developments of treatment. The current recommendations support sacral nerve modulation as the key treatment for faecal incontinence. They do not support the use of sphincter substitutions except in certain circumstances. Transanal irrigation is a novel often successful treatment of faecal incontinence due to neurological disorders.